Education for Sustainable Development and Inclusive Education with particular consideration of learners with special needs: a scoping literature review - Rončević, Katarina; Rieckmann, Marco (Frontiers in Education, 2025)
To date, Education for Sustainable Development (ESD) and Inclusive Education have largely been treated as separate pedagogical approaches. Inclusion-oriented ESD, in particular, has not been widely adopted in formal education settings. As this is a relatively new area of research, we started by providing an understanding of inclusion-oriented ESD focusing on learners with special needs. Subsequently, we conducted a scoping literature review to explore how inclusion-oriented ESD is addressed in peer-reviewed journals, focusing on school-related education. Limiting the review to articles in English and German contributed to a predominant focus on European contexts, introducing potential language and database selection biases. We analyzed 20 peer-reviewed articles using quantitative and qualitative content analysis with MAXQDA software. The findings suggest that inclusion-oriented ESD constitutes an emerging yet insufficiently explored area of research. Most contributions examine the normative connection between ESD and Inclusive Education, with an emphasis on shared ethical principles such as empowerment and social justice. However, concrete examples and actionable guidance for implementation are largely absent. While only a limited number of studies specifically address the needs of learners with disabilities, those that do underscore the significance of structured learning environments and the professional competencies of educators. The review concludes that a comprehensive approach to inclusion-oriented ESD—integrating pedagogical frameworks, institutional support structures, and an inclusive school culture—is urgently required.